The Neolithic of Sharbithāt (Dhofar, Sultanate of Oman): typological, technological, and experimental approaches - Maiorano, Maria Pia; Marchand, Grégor; Vosges, Jérémie; Berger, Jean-François; Borgi, Federico; Charpentier, Vincent (Proceedings of the Seminar for Arabian Studies, 2018)
Located between the last fringes of the al-Wusṭā Region and the plain of Dhofar (Ẓufār), the coastal plain of Sharbithāt has been scarcely explored. With its 14 km-long shoreline, its succession of wide terraces and wadi deltaic branches, and its abundant flint sources Sharbithāt represents one of the most promising Neolithic archaeological areas of the Omani coast. A first campaign in this area was therefore undertaken in January 2017 within the framework of the expedition programme 'Archaeology of the Arabian Seashores' and of the NeoArabia Project of the Agence nationale de la recherche (ANR). The Middle Holocene occupation in the surveyed terraces and low plateaus is particularly dense. Sites SHA-2, SHA-7, and SHA-10 revealed the presence of Neolithic dwellings (Late Neolithic period 2, c.4500-3100 BC) Moreover, in addition to the ordinary fishing equipment that characterizes this period, an astonishing lithic industry was also discovered. It consists of lunates, backed bladelets, and points made on flakes, similar to the so-called 'Fasad points' dating to the Early Holocene. The latter evidence suggests the use of this point type for a period longer than previously supposed or their attribution to the Late Neolithic, raising important chronological questions that must be carefully tested. Middle Neolithic occupation (c.6500-4500 BC) has also been identified at Sharbithāt SHA-4, an exceptional site that provided stone structures, at least one burial, many bifaces, several 'façonnage' products, and dozens of arrowheads with trihedral-shaped distal and plano-convex mesial. These types of projectile points were already known in the Ḥaḍramawt area in contexts dated between the sixth and fifth millennium but their chronological horizon in Oman must be further detailed with new dates.